A STUDY OF FACTORS THAT NEGATIVELY AFFECT THE EFFECTIVENESS OF GRINDER DEVICES - Mustafayev Oybek Bobomuradovich; Boltayev Muhammad A’zamovich; Ruziyeva Shahnoza Xayrullayevna; Axmedov Soyibjon Tojiboyevich (Web of Journals Publishing, 2024)
The mountain crusher is the highest loaded and bulk of the drilling equipment. Much of the contribution of the operational efficiency of drilling equipment is due to the work of mountain precision flicker tools, and it has been found that many factors influence the work of a mountain flicker tool.
Keywords: Dolota, axial power, washing beloved, skvajina, Slam.